MEC554: Thermalfluids Lab / College of Engineering - UiTM, College of Engineering (2023)
The course consists of two parts, i.e. topics in thermodynamics and fluid mechanics. It provides the opportunity for the students to operate, under supervision, various experimental equipments. Students shall complete with confidence all laboratory experiments and to relate them to theoretical understandings of thermofluids.